The role and influence of intelligent systems on technological progress and on the world as a whole - Fesenko, O. K.; Simkina, Marharyta; Сімкіна, Марина Володимирівна; Симкина, Марина Владимировна (ТДАТУ, 2019)
These facts and conclusions indicate a clear connection between the field of cybernetics and biology, neurophysiology, and philosophy, but still, despite the obvious problem of artificial intelligence, in the implementation of this kind of concept, this area continues to develop and attempts are made to recreate such algorithms, which have even found application in many areas of human activity.
Keywords: intelligent systems; scientific and technological progress; development of the sphere of cybernetics